Knowledge, attitude and stigma towards HIV patients: a survey among medical students in Tuzla, Bosnia and Herzegovina - Jahić, Rahima; Porobić-Jahić, Humera; Žepić, Denis; Piljić, Dilista; Petrović, Jasminka; Čustović, Amer (The Journal of Infection in Developing Countries, 2020)
Introduction: This survey aims to assess knowledge, attitude and stigma towards HIV patients, among medical students in Tuzla, Bosnia and Herzegovina. We also aimed to assess potential risk factors for HIV infection among fourth year medical students. Methodology: Data were collected from specific questionnaire that was completed by 171 students of the Faculty of Medicine, University of Tuzla. A multivariable logistic regression was performed. Results: Majority of students (79%) had a good knowledge of HIV, (median value of correct answers was 9 (95%) with at least 6 correct responses). Also, majority of students (73.6%) had a positive attitude towards HIV patients and the median positive value was 6 (95% CI: 6-7). More than a third of students considered that all hospitalized patients should be tested for HIV. Total of 81% of students considered that they should inform the sexual partner of HIV positive patient, although she/he disagrees. 61.4% of students had a discriminatory attitude towards HIV, with the median values of 3 (95% CI: 3-3). Multivariate regression analysis identified positive attitude towards HIV patients as an independent predictor for a non-discriminatory attitude. Moreover, an overall attitude towards HIV patients defines student`s determination to work with AIDS population. Male gender, and older age, were identified as predictors of risky behavior. Conclusions: Preventive measures, including better HIV education, are crucial. Knowledge can increase awareness of HIV infection, decrease the incidence and reduce stigma towards HIV patients.